The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1088/2752-5309/acb22b
|View full text |Cite
|
Sign up to set email alerts
|

Health impacts of smoke exposure in South America: increased risk for populations in the Amazonian Indigenous territories

Abstract: Smoke particulate matter emitted by fires in the Amazon Basin poses a threat to human health. Past research on this threat has mainly focused on the health impacts on countries as a whole or has relied on hospital admission data to quantify the health response. Such analyses do not capture the impact on people living in Indigenous territories close to the fires and who often lack access to medical care and may not show up at hospitals. Here we quantify the premature mortality due to smoke exposure of people li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Accurately assessing the extent of BA is key to understanding the effects of fires on Amazonian ecosystems [126], on society [127] and on the global carbon cycle [63,128], as well as ensuring good communication in national reports, and for decision-makers, more efficient actions to manage and prevent these events. Despite the significant contribution of global products, we have shown that, regionally, the use of these products can be critical in underestimating the total area burned and, consequently, fire-related impacts.…”
Section: Discussionmentioning
confidence: 99%
“…Accurately assessing the extent of BA is key to understanding the effects of fires on Amazonian ecosystems [126], on society [127] and on the global carbon cycle [63,128], as well as ensuring good communication in national reports, and for decision-makers, more efficient actions to manage and prevent these events. Despite the significant contribution of global products, we have shown that, regionally, the use of these products can be critical in underestimating the total area burned and, consequently, fire-related impacts.…”
Section: Discussionmentioning
confidence: 99%